Ramusella (Insculptoppia) insculpta - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Ramusella (Insculptoppia) insculpta (Paoli, 1908) Material – One specimen in Saraycık Forest Processing Area, Taşköprü, N 41° 18′ 10.00′′, E 34° 25′ 48.64′′, alt. = 1277 m, 10 July 2018, P. sylvestris, dead tree; one specimen in Karadedeoğlu Village Tekkeyaylası Area, Taşköprü forest, N 41° 22′ 55.26′′, E 34° 24′ 19.06′′, alt. = 1177 m, 2 August 2018, P. nigra, dead tree; three specimens in Yeşiltepe Area, Akçaabat, Trabzon, N 41° 20′ 09.64′′, E 34° 25′ 58.98′′, alt. = 1327 m, 2 June 2018, tree trunk of P. abies . Previous record in Turkey – Erzurum (Baran and Ayyildiz 2004), Trabzon, Samsun (Ayyildiz 1989), Ankara (Çobanoğlu and Bayram 1998). Global distribution – Palaearctic. Ecology – All types of habitats.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 262, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Arachnida; Animalia; Biodiversity; Ramusella insculpta; Sarcoptiformes; Ramusella; Oppiidae; Taxonomy; 15. Life on land